Iodine-125 seeds combined with anlotinib in the treatment of recurrent retroperitoneal liposarcoma after surgery: a case report - Tang, Gaoyan; Zhang, Yuping; Meng, Wenjuan; Zhong, Shoubin; Feng, Hui; Yu, Guohua; Liu, Shuzhen; Li, Rui (Frontiers in Oncology, 2025)
Retroperitoneal liposarcoma (RPLS) is a rare malignant mesenchymal tumor originating in the retroperitoneal space. It is characterized by a low incidence, poorly understood etiology and pathogenesis, and diverse imaging and pathological manifestations. The malignancy of RPLS varies significantly among cases. Currently, surgical resection remains the primary treatment for primary retroperitoneal liposarcoma; however, the disease is associated with a high and rapid recurrence rate, which severely impacts patient prognosis. This study presents a case of recurrent retroperitoneal liposarcoma treated with iodine-125 seed implantation following surgical intervention. Due to the large tumor size, high risk of postoperative recurrence, and the challenges of accurately targeting postoperative radiotherapy, surgical re-intervention was deemed unsuitable. Consequently, a comprehensive treatment plan involving iodine-125 seed implantation combined with anlotinib therapy was formulated. The patient achieved stable disease control over a 3-year follow-up period, demonstrating the potential efficacy of this combined therapeutic approach. This case highlights the antitumor potential of iodine-125 seed implantation combined with anlotinib in the management of retroperitoneal liposarcoma, particularly in cases where surgical options are limited.